2019
DOI: 10.3390/app10010243
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Filter Based on Fuzzy Techniques for Mixed Noise Reduction in Color Images

Abstract: To decrease contamination from a mixed combination of impulse and Gaussian noise on color digital images, a novel hybrid filter is proposed. The new technique is composed of two stages. A filter based on a fuzzy metric is used for the reduction of impulse noise at the first stage. At the second stage, to remove Gaussian noise, a fuzzy peer group method is applied on the image generated from the previous stage. The performance of the introduced algorithm was evaluated on standard test images employing widely us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…As a result of this process, a single output variable is passed. The input and output values are determined according to the training data [28,29].…”
Section: Reconstructing Images: Fuzzy Color Techniquementioning
confidence: 99%
“…As a result of this process, a single output variable is passed. The input and output values are determined according to the training data [28,29].…”
Section: Reconstructing Images: Fuzzy Color Techniquementioning
confidence: 99%
“…The major problems faced by machine learning-based models are the lack of efficient feature extraction and pre-processing of input images. In [20] , [21] the author showed that pre-processing through the Fuzzy color image enhancement technique can significantly improve feature extraction of computer vision models and hence improve the classification performance.…”
Section: Related Workmentioning
confidence: 99%
“…This greatly reduces the number of data [33]. The enlargement and reduction methods can adjust the range by enlarging or reducing the image when there is a large or small amount of data in the image [34]. The rotation and transformation methods are used when the object to be detected in the image is not in the designated form [35].…”
Section: Image Pre-processing Using Object Detectionmentioning
confidence: 99%